Characterization of Chitosan Films for Tissue Engineering Applications - A. Ghanem; M. Katalinich (Applied Bionics and Biomechanics)
Chitosan (β-(l,4)-2-amino-2-deoxy-D-glucose) is a naturally occurring, abundant biopolymer with desirable biomedical material properties of biodegradability, low toxicity, and good biocompatibility. These properties indicate that chitosan may be suitable as a surface for mammalian cell growth and tissue engineering. The attachment and growth of NIH-3T3 fibroblasts on chitosan films and controls was measured. Chitosan films of 0.5, 1.5, and 3.0% (w/v) support the attachment and proliferation of NIH-3T3 fibroblasts at rates slightly lower than polystyrene controls. The film tensile properties, surface roughness, and surface free energies indicate that the film-formation technique gives films with reproducible physical and chemical properties. Our results indicate that UV–IR treatment of chitosan films can change the water in air (WIA) contact angle and surface free energy (SFE) of the films, and can potentially be used to optimize the attachment and spreading of fibroblasts on these films. The ability of these chitosan films to support cell attachment and growth indicates their potential use as biomedical surfaces. This research may result in the development of biodegradable tissue-engineering matrices.